Survei Motivasi Berprestasi Atlet pada Club Petuanan Wailete Desa Hative Besar Kota Ambon - Juan Carlos Talahaturusun; Jonas Solissa; Mariana D. Hukubun (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
This research was conducted to find out the achievement motivation of athletes at the Petuanan Wailete club, Hative Besar village, Ambon City. The research method uses a survey method with a qualitative approach. The instrument used in the study was a questionnaire (questionnaire). Compile a statement with steps: 1) compiling concept definitions; 2) compiling operational definitions; 3) preparation of achievement motivation instrument grids, 4) compiling statements; related to the preparation of statements is not done because it uses standardised statements related to achievement motivation. That athletes who have low or less achievement motivation are 58 per cent, namely there are 18 athletes. 12.9 percent, namely 4 athletes, have moderate achievement motivation or sufficient category. While athletes who have high achievement motivation with a percentage of 39 per cent there are 9 athletes. Thus, the athlete's achievement motivation at the Wailete petuanan club in Hative Besar Village is in the lower category.